Communication of Da'wah Nahdlatul Ulama Dawah Institution (LDNU) in Preventing Hoax News - Mustafirin Mustafirin; Hatta Abdul Malik (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2021)
This study aims to find out how the efforts made by LDNU in building public perception to prevent hoax news through the mass media. The research was conducted with a da'wah communication approach to build awareness of the phenomenon of hoax news. The research was conducted through a qualitative approach through a meta-analysis of the literature. Meta-analysis is a unique technique used to create an integrative or methodology review. First, LDNU creates social media accounts for news education and control; second, LDNU cooperates with the media and other institutions to narrow the space for slander and hoaxes; third, LDNU continues to use the basis of the ITE Law as a guide in the use of social media. Eight management principles are applied as an integral part in building awareness, perception, knowledge, skills, and social responsibility in preventing the spread of hoax news and other harmful content.